Shifting techniques and multi-platform services for carbon efficiency - Tirel, Nicolas; Ilarri, Sergio; Roose, Philippe; Noureddine, Adel; Le Goaër, Olivier (Jornada de Jóvenes Investigadores del I3A, 2024)
The impact of IT on climate change is growing rapidly. We aim to develop a data model that evaluates the carbon footprint of digital services, along with a visualization tool to inform users. Besides, we intend to propose new services to reduce carbon emissions when computing workload, adapting the moment, the location or with leaner processing.